Structure and variability in human tongue muscle anatomy. Issue 5 (3rd September 2018) - Stone, Maureen; Woo, Jonghye; Lee, Junghoon; Poole, Tera; Seagraves, Amy; Chung, Michael; Kim, Eric; Murano, Emi Z.; Prince, Jerry L.; Blemker, Silvia S.
Abstract: The human tongue has a complex architecture, consistent with its complex roles in eating, speaking and breathing. Tongue muscle architecture has been depicted in drawings and photographs, but not quantified volumetrically. This paper aims to fill that gap by measuring the muscle architecture of the tongue for 14 people captured in high-resolution 3D MRI volumes. The results show the structure, relationships and variability among the muscles, as well as the effects of age, gender and weight on muscle volume. Since the tongue consists of partially interdigitated muscles, we consider the muscle volumes in two ways. The functional muscle volume encompasses the region of the tongue served by the muscle. The structural volume halves the volume of the muscle in regions where it interdigitates with other muscles. Results show similarity of scaling across subjects, and speculate on functional effects of the anatomical structure.